The Effect of Goat Milk Substitution with Ketapang Seed Extract (Terminalia catappa L.) in the Making of Optima Kefir on WHC, Syneresis, and Organoleptics - Nurdestianty, Kania; Wulandari, Eka; Pratama, Andry (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
The purpose of this study was to determine the effect of goat milk substitution with ketapang seed extract on the manufacture of kefir, and to obtain the best concentration on WHC, syneresis, and kefir organoleptic. The study was conducted experimentally using a Completely Randomized Design with 5 treatments (P1 = 80:20, P2 = 60:40, P3 = 50:50, P4 = 40:60, P5 = 20:80) and 4 repetitions. WHC and syneresis data were analyzed using analysis of variance and Duncan's advanced test, while organoleptic data were analyzed using Kruskal-Wallis and Mann-Whitney advanced tests. The results showed that goat milk substitution with ketapang seed extract had a significant effect on syneresis but did not have a significant effect on WHC, and had a significant effect on organoleptic color, aroma, texture, and total acceptance, but did not have a significant effect on kefir taste. The ratio of 80:20 was the best ratio with WHC 57.32%, syneresis 39.00%, and preferred kefir organoleptic.